2018
DOI: 10.1371/journal.pone.0202507
|View full text |Cite
|
Sign up to set email alerts
|

At 4.5 but not 5.5 years, children favor kin when the stakes are moderately high

Abstract: Adults report more willingness to help siblings over close friends when the stakes are extremely high, such as when deciding whether to donate a kidney or risk injury to rescue someone in peril. When dividing plentiful, low-value resources, in contrast, children expect people to share equally with friends and siblings. Even when distributing limited resources—one instead of many—and distributing to their own social partners rather than fictional characters, children share more with kin and friends than with st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
(53 reference statements)
0
3
0
Order By: Relevance
“…These results are interesting in that they are among the first evidence that young children differentiate between friends and family. Although previous research found that children value friends and family over strangers (Olson & Spelke, 2008; Spokes & Spelke, 2016), children typically behave similarly toward friends and family (but see Spokes & Spelke, 2018 for one example where the two are treated differently). Finally, as in the previous experiments, many effects got stronger with age, indicating that older children show greater support than younger children for the ‘Selective Inferences’ hypothesis.…”
Section: Discussionmentioning
confidence: 98%
“…These results are interesting in that they are among the first evidence that young children differentiate between friends and family. Although previous research found that children value friends and family over strangers (Olson & Spelke, 2008; Spokes & Spelke, 2016), children typically behave similarly toward friends and family (but see Spokes & Spelke, 2018 for one example where the two are treated differently). Finally, as in the previous experiments, many effects got stronger with age, indicating that older children show greater support than younger children for the ‘Selective Inferences’ hypothesis.…”
Section: Discussionmentioning
confidence: 98%
“…Parent/guardian reported educational attainment (mean percentages of Caregivers 1&2): M = 47.1% did not complete the optional demographic form, M = 3.9% High school or equivalent, M = 2.9% Community college/vocational school, M = 21.2% 4-year college/university degree, M = 25.0% professional/graduate school. 6 As some research has found that youg children are not always able to distinguish between friends and family (Spokes & Spelke, 2018), an additional exploratory analysis was conducted of children's verbal responses to these open-ended prompts in order to validate the testing procedure and offer additional insight on children's causal reasoning about mutual intentionality and group membership. Please refer to the Supplemental Materials to view this analysis.…”
Section: Stimuli Design and Proceduresmentioning
confidence: 99%
“…Furthermore, some research suggests that young children may not readily differentiate between siblings and friends (Spokes & Spelke, 2018), so it is possible that participants in Study 1 were not viewing the prescribed categories as intended by the researchers (e.g., confusing the family as a friend group). To account for this, we conducted a text-analysis of the open-ended participant responses from Study 2 to assess the language being used in reference to the different group conditions as a proxy of the children's understanding of each group's intended categorization.…”
mentioning
confidence: 99%